PEACH Score Validation of Postoperative In-Hospital Mortality in Adult Congenital Heart Disease Patients at Haji Adam Malik General Hospital Medan - Zebua, Juang Idaman; Nasution, Ali Nafiah; Ketaren, Andre Pasha; Hasan, Harris; Akbar, Nizam Zikri (Jurnal Kardiologi Indonesia, 2025)
In “PEACH Score Validation of Postoperative In-Hospital Mortality in Adult Congenital Heart Disease Patients at Haji Adam Malik General Hospital Medan” (Indonesian Journal of Cardiology, 44(2), 61-7. https://doi.org/10.30701/ijc.1546), there is an error noted. An error has been found in the PDF version of this article. The DOI printed in the PDF is incorrect. The correct DOI is https://doi.org/10.30701/ijc.1546. The error occurs only in the PDF; the DOI listed in the article metadata is already correct.The publisher apologizes for any inconvenience caused by this error.DOI of original article: https://doi.org/10.30701/ijc.1546